2020
DOI: 10.3390/antiox9030205
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect and Mechanism of Action of Quercetin and Quercetin Diels-Alder anti-Dimer on Erastin-Induced Ferroptosis in Bone Marrow-Derived Mesenchymal Stem Cells

Abstract: In this study, the anti-ferroptosis effects of catecholic flavonol quercetin and its metabolite quercetin Diels-Alder anti-dimer (QDAD) were studied using an erastin-treated bone marrow-derived mesenchymal stem cell (bmMSCs) model. Quercetin exhibited higher anti-ferroptosis levels than QDAD, as indicated by 4,4-difluoro-5-(4-phenyl-1,3-butadienyl)-4-bora-3a,4a-diaza-s-indacene-3-undecanoic acid (C11-BODIPY), 2′,7′-dichlorodihydrofluoroscein diacetate (H2DCFDA), lactate dehydrogenase (LDH) release, cell counti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 83 publications
0
41
0
Order By: Relevance
“…The MS/MS spectra showed that the quasi-molecular ion of the dimeric product from Q was 601.2 m / z , with only one fragment ion at 299.0 m / z . Considering the MW of Q (302.24), the result indicated that the dimer was one of a quercetin Diels–Alder dimer ( Figure 5 E) [ 32 ]. A likely pathway for the dimer formation is one quercetin losing H atoms and being converted to an o -quinone, which gives a Diels–Alder reaction with another quercetin to form the dimer with an MW of 602.…”
Section: Resultsmentioning
confidence: 99%
“…The MS/MS spectra showed that the quasi-molecular ion of the dimeric product from Q was 601.2 m / z , with only one fragment ion at 299.0 m / z . Considering the MW of Q (302.24), the result indicated that the dimer was one of a quercetin Diels–Alder dimer ( Figure 5 E) [ 32 ]. A likely pathway for the dimer formation is one quercetin losing H atoms and being converted to an o -quinone, which gives a Diels–Alder reaction with another quercetin to form the dimer with an MW of 602.…”
Section: Resultsmentioning
confidence: 99%
“…Many researchers have reported the biomedical applications of herbal medicines [ 346 , 347 , 348 , 349 , 350 , 351 , 352 , 353 , 354 , 355 , 356 , 357 , 358 , 359 , 360 , 361 , 362 , 363 , 364 , 365 ]. Antibiotics and other chemical antimicrobial agents including metal oxide and metal nanoparticles can inhibit bacteria growth but also lead to ROS generation and other side effects.…”
Section: Conclusion and The Future Outlookmentioning
confidence: 99%
“…QCT was also reported to possess protective effect on diabetic nephropathy [16] , and even have the ability of iron chelation [17] , [18] . Another recent publication reported that QCT could protect bone marrow-derived mesenchymal stem cell from erastin-induced ferroptosis, possibly through the antioxidant pathway [19] . In spite of the attention QCT drew and the wide effects already discovered, the effect of QCT on AKI ferroptosis remains undescribed.…”
Section: Introductionmentioning
confidence: 99%